The p38/MK2 Axis in Monocytes of Fibromyalgia Syndrome Patients: An Explorative Study - Boya Nugraha; Renate Scheibe; Christoph Korallus; Matthias Gaestel; Christoph Gutenbrunner (Medicina, 2021)
Background and Objectives: The aetiology and pathomechanism of fibromyalgia syndrome 12 (FMS) as one of chronic pain syndromes still need to be further elucidated. Mitogen-activated protein kinase (MAPK) pathway has been proposed as a novel approach in pain management. Since the major symptom of fibromyalgia syndrome (FMS) patients is pain, it became of interest whether MAPK pathways, such as the stress-activated p38 MAPK/MK2 axis, are activated in FMS patients. Therefore, this study aimed at determining p38 MAPK/MK2 in FMS patients. Materials and Methods: Phosphorylation of MAPK-activated protein kinases 2 (MK2), a direct target of p38 MAPK, was measured in monocytes of FMS and healthy controls (HCs) to monitor the activity of this pathway. Results: The mean level of phosphorylated MK2 was fivefold higher in FMS patients as compared to HCs (p < 0.001). Subgroup analysis revealed that antidepressants did not influence the activity of MK2 in FMS patients. Conclusions: This result indicates that the p38/MK2 pathway could be involved in the pathomechanism of FMS, could act as a clinical marker for FMS, and could be a possible target for pain management in FMS patients.